One-dimensional spindle-like BiVO4/TiO2 nanofibers heterojunction nanocomposites with enhanced visible light photocatalytic activity. Issue 3 (15th February 2016) - Guo, Zengcai; Li, Ping; Che, Hongwei; Wang, Guangshuo; Wu, Chunxia; Zhang, Xiaoliang; Mu, Jingbo
Abstract: One-dimensional spindle-like BiVO4 /TiO2 nanofibers heterojunction nanocomposites with high visible light photocatalytic activity have been successfully obtained by combining the electrospinning technique and solvothermal method. The as-obtained products were characterized by field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), UV–vis spectra and photoluminescence (PL) spectra. The results revealed that spindle-like BiVO4 nanostructures were successfully grown on TiO2 nanofibers. Photocatalytic tests showed that the BiVO4 /TiO2 nanofibers heterojunction nanocomposites showed enhanced visible light photocatalytic activity than that of pure TiO2 nanofibers, which might be attributed to the effective photogenerated electrons-holes separation based on the photosynergistic effect of the BiVO4 /TiO2 heterojunction. Moreover, the BiVO4 /TiO2 nanofibers heterojunction nanocomposites could be easily recycled without any decrease of the photocatalytic activity.